Investigations on pre and post emergence mortality in eggplant (Solanum melongena L.) - DATAR*, V.V. (Indian Phytopathology, 2007)
Pre and post emergence damping off in eggplant was 29-30 % in cv ABV-1. The fungus Fusarium equiseti (Corda)Sacc. was highly pathogenic. Association of nematode Meloidogyne incognita and fungus was synergistic. Lowest darning off was observed when Neem cake was added to soil followed by ambadi, cotton and safflower cake. Soil solarization and rabbing of soil was effective in reducing damping off. Trichoderma harzianum and Aspergillus niger exhibited antagonistic activity against the pathogen. Seed treatment with T. harzianum @ 10g1 kg seed + soil application of T. harzianum @ 20g 1 pot showed minimum damping off. Seed treatment with captan or Thiram @ 3 gml kg was best in reducing damping off. Lowest damping off was observed in formaldehyde 5% drenching. Integrated management of damping off was obtained with soil sterilization with 5% formaldehyde drenching + seed treatment with thiram @ 3gm Ikg seed + drenching of copper oxychloride @ 0.3 %.